Evaluation of Alvarado scoring system (MANTRELS scoring) as a diagnostic aid in preoperative diagnosis of acute appendicitis at Nalanda Medical College and Hospital, Patna - Shekhar, Raj; Gupta, V. K. (International Surgery Journal, 2020)
Background: Acute appendicitis is one of the commonest surgical emergencies. The rate of negative appendicectomy has been reported to be between 20-30%. The aim of this study is to evaluate the efficacy of Alvarado scoring system in cutting down the rate of negative appendicectomy without increasing morbidity and mortality. Methods: A study of 100 patients presenting with pain abdomen and diagnosed provisionally as acute appendicitis, was undertaken. Depending on individual presentation, a score was calculated for each case, based on Alvarado scoring system. Operative and conservative intervention was undertaken in patients with scores between 5 and 10 and <5 respectively. The results of Alvarado scoring system, on table operative findings and HPE, were reviewed. Results: A total of 94 patients with score of 7-10 and 5-6 were operated. Among males with score of 7-10, 33 patients were operated and 31 were found to have inflamed appendix. Among females with score of 7-10, 33 patients were operated and 28 were found to have inflamed appendix. The sensitivity of Alvarado scoring system in males with score of 7-10 was found to be 81.57% and among females with score of 7-10 was found to be 75.67%. Conclusions: The Alvarado scoring system is a fast, simple, reliable, non-invasive, repeatable and safe diagnostic modality without extra expense and complications.